Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/bab.1649
|View full text |Cite
|
Sign up to set email alerts
|

Advances in ginsenoside biosynthesis and metabolic regulation

Abstract: In this paper, we reviewed the advances in ginsenoside biosynthesis and metabolic regulation. To begin with, the application of elicitors in the ginsenoside biosynthesis was discussed. Methyl jasmonate (MJ) and analogues have the best effect on accumulation of ginsenoside compared with other elicitors, and few biotic elicitors are applied in Panax genus plants tissue culture. In addition, so far, more than 40 genes encoding ginsenoside biosynthesis related enzymes have been cloned and identified from Panax gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Ginsenoside, a saponin specific to ginseng, is classified according to the number of hydroxyl group bound to structure as either PPD (protopanaxadiol) or PPT (protopanaxatriol). It has been reported that the composition and content of ginsenoside varies depending on a variety of other conditions including the region in which it is cultivated and its growth environment (Lu et al, 2018). The extraction yields of crude saponin from the roots of 1YHPG, 2YHPG, 4YSCG, and 6YSCG, and the shoots of 1YHPG and 2YHPG, were 8.24, 9.67, 8.98, 7.49, 26.36, and 33.33%, respectively (data not shown).…”
Section: Ginsenoside Contentmentioning
confidence: 99%
“…Ginsenoside, a saponin specific to ginseng, is classified according to the number of hydroxyl group bound to structure as either PPD (protopanaxadiol) or PPT (protopanaxatriol). It has been reported that the composition and content of ginsenoside varies depending on a variety of other conditions including the region in which it is cultivated and its growth environment (Lu et al, 2018). The extraction yields of crude saponin from the roots of 1YHPG, 2YHPG, 4YSCG, and 6YSCG, and the shoots of 1YHPG and 2YHPG, were 8.24, 9.67, 8.98, 7.49, 26.36, and 33.33%, respectively (data not shown).…”
Section: Ginsenoside Contentmentioning
confidence: 99%
“…With minor improvements in cultivation parameters, an economical large-scale bioprocess can be developed, replacing expensive chemical synthesis that requires protection and deprotection reactions, resulting in low specificities and yields. Various terpene glycosides occur naturally and are obtained in small amounts from plant extracts [ 48 , 62 , 63 ]. Due to their high economic importance, glycosylation using enzyme biocatalysts becomes very attractive for the synthesis of glycosides and exhibits high efficiency, stereoselectivity and regioselectivity in an environmentally friendly manner.…”
Section: Discussionmentioning
confidence: 99%
“…JA responsive genes involved in ginsenoside biosynthesis are regulated by different TFs 161 , 162 , 163 . MeJA and its analogues, the best effective elicitor on ginsenoside accumulation, were often used to stimulate ginsenoside biosynthesis in plant tissue cultures 52 . (+)-7- iso -Jasmonoyl- l -isoleucine (JA-Ile) was considered as the endogenous bioactive jasmonate 164 , and MeJA was cleaved by esterases and subsequently converted to JA-Ile by JA-amino acid synthetase (JAR1) before working as an elicitor 165 .…”
Section: Regulatorsmentioning
confidence: 99%
“…Application of elicitors are effective to improve ginsenoside production. Among these elicitors, MeJA and its analogues were most effective 52 . In a MeJA elicited experiment, all the MVA pathway genes except IDI were up-regulated.…”
Section: Biotechnological Approaches For Ginsenoside Productionmentioning
confidence: 99%
See 1 more Smart Citation